(untitled) (Acta Scientiarum. Biological Sciences, 2013)
This study aimed to describe the early development of Clarias gariepinus, a species that has been introduced into various watersheds worldwide, in order to help the identification of its eggs, larvae and juveniles in natural environments. The material used was obtained via induced spawning during 1999. After spawning, the periodicity of sampling varied according to ontogenic development. We analyzed 12 eggs, 146 larvae and 6 juveniles. Newly fertilized eggs are spherical, with a double membrane, the density of which varies. Initially the larvae have little pigmentation but this intensifies during development. They have four pairs of well-developed barbels, an elongated body, long dorsal and anal fins, no adipose fin and vesicles surrounding the finfold and barbels. The sequence of formation of the fins is: caudal, dorsal, anal, pectoral and pelvic. Growth pattern analysis revealed that metamorphosis usually occurs during the flexion stage. The reproductive performance of the species and its rapid early development favor aquaculture; however, they may also favor its invasion of natural environments, representing a threat for native populations.